MINERALOGY OF THE SAHARAN AEOLIAN DUST IN CRETE: EXAMPLES FROM THE PERIOD 2004-2009 - Christidis, G.E.; Perdikatsis, V; Apostolaki, Ch. (Bulletin of the Geological Society of Greece, 2010)
Aeolian dust sediments, which were deposited by spring rainstorms or directly by the dust cloud were collected in the Technical University of Crete during the interval 2004-2009. The samples display remarkable mineralogical homogeneity and consist of illite, quartz, calcite, albite, kaolinite, palygorskite and dolomite. Chlorite or/and smectite is present in samples collected in 2006 and 2009. Gypsum is present in the collected from the airborne dust in 2009, but not from the sample which precipitated from rain in the same day. Mirabilite was traced in the sediment collected in 2005. The presence of palygorskite and dolomite in all samples and gypsum and mirabilite in two of the collected sediments implies formation of the original material in an arid environment characterized by alkaline pH. The mineralogical composition coupled with back trajectory analysis on similar dust clouds indicate that the clouds originated in areas of Western Sahara or/and southern Morocco and that major mixing with fine-grained material from Europe is less probable. The possibility for a Central Algerian source for the airborne dust clouds is rejected because of the lack of smectite.